1993
DOI: 10.1007/bf03348950
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of intact human chorionic gonadotropin (HCG) and its free a and β subunits, in relation to maternal thyroid stimulation during normal pregnancy

Abstract: The main objective of the present study was to present additional evidence of the potentially important thyrotropic role of hCG to regulate the maternal thyroid gland during normal pregnancy. Sequential determinations (first and last trimesters) of intact hCG, free alpha and beta-hCG subunits concentrations (using monoclonal IRMAs), and assessment of parameters of thyroid function and thyroid volume were carried out in 62 pregnant women who exhibited during the first trimester of gestation low TSH levels (< or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(74 citation statements)
references
References 28 publications
2
68
0
3
Order By: Relevance
“…This is consistent with other studies which have reported that resolution of hyperthyroidism occurs within a time frame of 1-10 weeks 1 . Glinoer et al 7 showed that hCG remained abnormally elevated for several weeks during the second trimester and that normalisation of free T4 levels paralleled the decline in hCG, supporting its role in the pathogenesis of transient hyperthyroidism of hyperemesis gravidarum. Unfortunately, our study did not look at hCG levels.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This is consistent with other studies which have reported that resolution of hyperthyroidism occurs within a time frame of 1-10 weeks 1 . Glinoer et al 7 showed that hCG remained abnormally elevated for several weeks during the second trimester and that normalisation of free T4 levels paralleled the decline in hCG, supporting its role in the pathogenesis of transient hyperthyroidism of hyperemesis gravidarum. Unfortunately, our study did not look at hCG levels.…”
Section: Discussionmentioning
confidence: 95%
“…In a study that looked at TSH blunting in a large group of pregnant women during the three trimesters, 18% of women in the first trimester had transiently subnormal TSH levels (as well as higher mean hCG levels) with almost half being undetectable (<0.05 mU/L). Eleven percent of the women with undetectable TSH levels also had elevated free T4 levels 7 . Isolated TSH suppression therefore forms one end of this spectrum followed by the additional finding of elevated free T4 levels and finally, transient hyperthyroidism of hyperemesis gravidarum.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, 10%-20% of pregnant women may have serum TSH levels that are low compared to the range of TSH found in nonpregnant women (either subnormal or fully suppressed) without coexisting thyrotoxic symptoms. 25,71 When TSH is very low, a trend in the serum T 4 and T 3 serum levels may help in differentiating transient GTT from a truly thyrotoxic state. Therefore, more than just biochemistry is necessary for full confidence in the diagnosis.…”
Section: Hyperthyroidism and Pregnancymentioning
confidence: 99%
“…Placental production of human chorionic gonadotrophin (hCG) and a rise in oestrogen production that increases binding proteins, namely thyroxinebinding globulin affect free TH levels. TSH dips according to most but not all studies within the first trimester, whereas free TH concentrations decrease, albeit very slightly, mainly during the latter part of pregnancy (10,11,14,15,16,17,18,19). These observed alterations are not only due to pathophysiological changes but are, at least in part, due to methodological issues.…”
Section: Changes Of Tsh Ths and Iodine During Pregnancymentioning
confidence: 95%